LAND MANAGEMENT FOR SUSTAINABLE AGRICULTURE IN NORTH COASTAL PLAIN, BALI 1 - Budiasa, I Wayan (Bumi Lestari; Vol 8 No 1 (2008), 2012)
Intensive farming system development will lead to trade-off between economic benefits in the short run and environmental problems, especially critical soil erosion in the long run. The excessive erosion has reduced soil quality, then caused rapid reduction in land productivity or even made the land unsuitable for agriculture. If agriculture is to become sustainable, land management must be considered as one of best management practices in farming system development. A research in Tembok Village, Buleleng Regency, Bali aims to assess land suitability, soil fertility, soil erosion and conservation, and soil nutrient management for irrigated mixed farming system in north coastal plain of Bali. It is found that coastal area in the study area is classified into poor fertile soil due to the low level of cation exchangeable capacity and organic matter content. It is potentially categorized as marginal suitable (S3) for maize, cassava, groundnuts, sweet potato, melon, chili, banana, cashew, coconut, and palmyra palm; and suitable enough (S2) for mango, papaya and fodder grasses. The erosion level was very light by 2.036 t/ha/yr. This level has good relation with the erosion level by 2.04 t/ha/yr from laboratory experiment result by Sukartaatmadja et al. (2003) with similar characteristic of land and cow manure dosage requirement by 5 t/ha/yr. To improve soil fertility and to keep soil erosion not more than 2.036 t/ha/yr, the minimum 5 t/ha/yr of manure should be added into soil.
Keywords: land suitability, soil fertility, erosion, sustainable agricult